Variation in greenhouse gas production within a thermokarst lagoon system, outer Mackenzie Delta, Canada ... - Jenrich, Maren (PANGAEA, 2025)
When highly degraded, lowland thermokarst landscapes are flooded by the sea, and thermokarst lagoons, lakes, and the sea become connected with each other, complex lagoon systems are formed. Consequently, a natural gradient of marine submergence age and connectivity emerges within the system with older, well-connected lagoons closer to the sea, and younger, less connected lagoons further inland. The dataset presents the cumulative greenhouse gas production and daily production rates from 7 lagoons of variing sea connectivity and permafrost and active layer as endmembers. In detail sediment of active layer (AL) and permafrost (PF) from a soil pit located on the lowland of Reindeer Island (RI21-P2-AL, RI21-P2-PF), a thermokarst lake (RI21-05 (TKL05)), a limited open lagoon (LAG13), two semi-open lagoons (LAG04; LAG14), two mostly open lagoons (LAG03; LAG16) and two open lagoons (LAG07; LAG12). We incubated the samples anaerobically at 4 °C under fresh (c=0 g/L), brackish (c=13g/L) and marine (36g/L) conditions ...